Dietary Protein and Changes in Biomarkers of Inflammation and Oxidative Stress in the Framingham Heart Study Offspring Cohort. Issue 5 (28th March 2019) - Hruby, Adela; Jacques, Paul F
ABSTRACT: Background: Chronic inflammation is thought to be a major characteristic of aging, which may increase need for substrates, specifically protein, to support anti-inflammatory processes. Objectives: The aim of this study was to assess associations between dietary protein and changes in biomarkers of inflammation and oxidative stress over the long term in a community-dwelling population. Methods: In 2061 participants of the Framingham Heart Study Offspring cohort who attended exams 7 (1998–2001; mean ± SD age 60.0 ± 8.8 y, 56% female) and 8 (2005–2008), total, animal, and plant protein intakes were assessed by food-frequency questionnaire at each exam, energy adjusted, and averaged. We defined an inflammation and oxidative stress score as the sum of rank-normalized values of 9 circulating biomarkers (C-reactive protein, osteoprotegerin, P-selectin, tumor necrosis factor receptor II, soluble intercellular adhesion molecule-1, interleukin 6, monocyte chemoattractant protein 1, and lipoprotein phospholipase A2 mass and activity), and urinary isoprostanes, along with 2 subscores. Adjusted least-square means of changes in the scores and log individual biomarkers in quartile categories of intake were estimated with the use of linear regression models, across mean ± SD 6.6 ± 0.7 y of follow-up. Results: Protein intake was inversely associated with changes in the inflammation and oxidative stress score (mean ± SE in Q1 compared with Q4: 0.77 ± 0.17 compared with 0.31 ± 0.19; P -trend = 0.02), indicating overall inflammation/oxidative stress increased less in those with the highest intake than in those with the lowest. Favorable associations were observed for plant protein (Q1 compared with Q4: 0.89 ± 0.25 compared with 0.14 ± 0.25; P -trend = 0.001), but only trended toward significance for animal protein (Q1 compared with Q4: 0.70 ± 0.26 compared with 0.31 ± 0.26; P -trend = 0.05). Total protein and plant protein intakes were also inversely associated with changes in monocyte chemoattractant protein 1 (total: Q1 compared with Q4: 0.19 ± 0.01 compared with 0.15 ± 0.01 log-pg/mL; P -trend = 0.03; plant: Q1 compared with Q4: 0.21 ± 0.01 compared with 0.16 ± 0.01 log-pg/mL; P -trend = 0.003). Conclusions: Dietary protein, particularly from plant sources, may be associated with beneficial changes in the inflammatory burden in aging populations.